A admissibilidade da designação beneficiária nos fundos de pensões à luz do ordenamento jurídico português - Leitão, Vera Lúcia (2023)
The purpose of our analysis is to address the admissibility of the designation of a beneficiary in the context of pension funds under the Portuguese legal system, similar to what happens with other financial products to which a welfare function is attributed. To this extent, we propose to explore the legislative answer to the question of to whom should the retirement benefits agreed in the pension plan be paid from the moment of the death of its participant. And, in particular, in the situation where the participant designates, while still alive, a beneficiary for this purpose. The problem is complex and subsists in two ways. Firstly, because the applicable legal regime does not expressly foresee the possibility of the participant designating a beneficiary who upon his death will receive the benefits arising from the respective pension plan. Subsequently, having overcome this issue, the problem is to determine which legal regime applies to the right held by the beneficiary following that designation. We propose to explore the subsidiary application of the Insurance Contract Law. And also to understand if it is admissible to classify the designation of a beneficiary in pension funds as a contract in favour of a third party. Having built this path, we will reach the last point of our exposition. The analysis of the beneficiary designation as a contract in favour of a third party in the light of the law of succession to explore the possible applicability of the mandatory rules. In this perspective of analysis we also consider it particularly important to analyse, on a comparative basis, the beneficiary designation in retirement savings plans, considering that these also constitute products which, fulfilling a welfare purpose, provide for reimbursement through the payment of a retirement pension, similarly to what happens with pension funds.